DEVELOPING LEARNER AUTONOMY IN WRITING THROUGH THE USE OF E-PORTFOLIO - Fitri Aprianti; Eline Rozaliya Winarto (English Review: Journal of English Education, 2021)
Learner autonomy is mandated to be developed by the newest Curriculum of 2013. This research explored the use of E-Portfolio to develop learner autonomy especially in the area of leaner involvement, reflection, and target language use. The mixed method design involving the quantitative and qualitative data was used in this research. The data itself was collected in the naturalistic settings of two vocational high school classes. The two classes were taken from the population which consisted of 440 participants. Inventory tests were specifically designed to measure changes in the participants both before and after a writing program applying e-portfolio documents was given. Meanwhile, document analysis was used to indicate the development of learner autonomy in writing. The results of the initial inventory test show that the profile of initial autonomy development of the population was moderate which indicates that the participants had not yet reached the optimum capacity to carry active involvement, reflection, and target language use in writing it means that a type of preventive intervention such as that of e-portfolio was needed. Whereas, the results of the intervention or experimental study and document analysis suggest that there was an improvement regarding the degree of learner autonomy development. In this case, the results indicated that the requirements of the e-portfolio for the participant to constantly use the target language may have possibly supported the initial autonomy development in writing, while the participants’ independence in deciding aspects of writing in the e-portfolio may play a role in supporting the constructs of learner autonomy especially in terms of learner involvement, and lastly, the segment of learner reflection provided in the e-portfolio may have a critical role to play in the subsequent learner autonomy development of the participants.